Psicomotricidad y desarrollo cognitivo en niños de la institución educativa inicial N° 657 Simón Bolívar Punchana 2024 - Ushiñahua Lopez, Karen del Rosario (2025)
The current study aimed to examine the Early Childhood Education Institution No. 657 Simón Bolívar, Punchana, 2024, using a non-experimental design, correlational transactional type, and a student population of 91. The main data collection technique used in the study was observation, utilizing observation sheets to assess psychomotor skills and cognitive development. The results indicate that there is a significant correlation between expressive language through body expression and cognitive development (Kendall's Tau B = 0.690, with P < 0.001), as well as a positive correlation between gross and fine motor skills and cognitive development, with the respective motor factors showing corresponding coefficients. Finally, it can be concluded that there is a significant correlation between psychomotor and cognitive development (Kendall's Tau B coefficient = 0.863; P < 0.001).